Using Technology to Remove Embedded Ideologies From Leadership and Culture - Hamilton, Chris; Leonard, LaKesha; Uzoigwe, Chigo; Bell, Reginald L. (Journal of Leadership, Accountability and Ethics, 2024)
This study reviewed the related literature and ascertained a range of factors that shape and improve cultural awareness, with the critical findings poised to impact the overall organizational culture and performance associated with technology. The research question was simple. “What technology tools aid leaders in facilitating the removal of embedded ideologies that plague cultures?” The result of the literature review was a flow chart developed to explicate a framework for the synergistic use of technology tools to improve leadership. The study found that effective leadership fosters positive interactions, enhances performance, and establishes fair, non-stereotypical expectations. Six recommendations are given to foster synergistic technology delivery in facilitating the removal of embedded ideologies that plague corporate cultures.